(untitled) (Journal of Medical & Health Sciences Review, 2025)
DNA barcoding is a new perspective that uses gene sequence Cytochrome C oxidase subunit I (COI) for identification of unknown species by using "barcodes". The present study of” Labeo bata” specie was conducted for identification because it is important food specie in Pakistan. PCR products were analyized by bioinformatic tools. Evolutionary tree based on kimura 2 parameter indicate phylogenetic relationship among labeo species.A specimen is recognized if the barcode sequence of unknown specimen resembles the sequence in the barcode library or else, a new record is determined. It was concluded that DNA barcoding serves as milstone for identification at molecular level.